2020
DOI: 10.1186/s12940-020-00656-0
|View full text |Cite
|
Sign up to set email alerts
|

Perfluoroalkyl substances are associated with elevated blood pressure and hypertension in highly exposed young adults

Abstract: Background Residents in a large area of North-Eastern Italy were exposed to perfluoroalkyl substances (PFAS) via drinking water. Studies on the association between PFAS and blood pressure levels are limited, and results are inconsistent. Using cross-sectional data from the Regional health surveillance program, we aimed to quantify the associations between PFAS serum concentrations and blood pressure and hypertension prevalence. Methods … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
2

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 48 publications
(85 reference statements)
2
35
2
Order By: Relevance
“…Three cross-sectional studies reported significant positive associations of specific PFAS with prevalent hypertension and elevated blood pressure. [27][28][29] In a study of 2934 adults who participated in the 2003 to 2004 and 2005 to 2006 National Health and Nutrition Examination Survey, the adjusted odds for prevalent hypertension were 2 and a half-fold higher in those at the 80th versus the 20th percentiles of PFOA concentrations; no relationship was found for other PFAS. 27 A cross-sectional study of 1612 Chinese adults aged 22 to 96 years reported significant relationships of prevalent hypertension with PFOS, PFOA, perfluorononanoate, and perfluorobutanoate, with more pronounced effects observed in females; whereas no associations were detected for other compounds.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Three cross-sectional studies reported significant positive associations of specific PFAS with prevalent hypertension and elevated blood pressure. [27][28][29] In a study of 2934 adults who participated in the 2003 to 2004 and 2005 to 2006 National Health and Nutrition Examination Survey, the adjusted odds for prevalent hypertension were 2 and a half-fold higher in those at the 80th versus the 20th percentiles of PFOA concentrations; no relationship was found for other PFAS. 27 A cross-sectional study of 1612 Chinese adults aged 22 to 96 years reported significant relationships of prevalent hypertension with PFOS, PFOA, perfluorononanoate, and perfluorobutanoate, with more pronounced effects observed in females; whereas no associations were detected for other compounds.…”
Section: Discussionmentioning
confidence: 99%
“…25 Until recently, only one study has investigated the associations between PFAS exposure and incident hypertension, 26 with no relationship detected in a prospective cohort of 660 prediabetic and overweight adults. Three cross-sectional studies have linked certain PFAS to increased prevalence of hypertension and elevated blood pressure, [27][28][29] but 3 separate studies reported no association or even suggested protective effects of PFAS. [30][31][32] Given the ubiquitous nature of PFAS exposure, even a modest association between PFAS and hypertension would place a large number of people at increased risk for cardiovascular morbidity and mortality.…”
mentioning
confidence: 99%
“…In a small study in Chinese men (81 affected and 67 nonaffected by metabolic syndrome), circulating levels of PFOA and PFNA were significantly higher in the subjects with metabolic syndrome, and were also associated with blood pressure (58).Recently, Pitter and colleagues used data from the Regional health surveillance program in the Veneto region (Italy), including 15,786 individuals aged 20-39 years, and found that circulating PFAS concentration was associated with an increase in both systolic and diastolic blood pressure and with the prevalence of hypertension, the latter only in men. In particular, the difference in systolic and diastolic blood pressure from the lowest to highest decile of circulating PFOA was nearly 1.5 mmHg (63).…”
Section: Pfas-related Metabolic and Hypertensive Disordersmentioning
confidence: 90%
“…Besides, the study did not declare whether the area or neighbouring area has previously been exposed to army training sites or any industrial activities involving PFCs. Several reports had demonstrated that occupational exposure can be the reason for getting CVDs associated with contaminants [31,50,71].…”
Section: Discussionmentioning
confidence: 99%